Plan emergente para la recuperación de los microcréditos, en la cooperativa de ahorro y crédito Ambato LTDA. provincia de Cotopaxi cantón Latacunga durante el año 2014 - Chávez Chicaiza, Cumandá Lucía (2015)
This research provides information regarding an emergency plan for the recovery of microcredit in the Ambato credit union Ltda. In order to reduce the default rate on microloans so that improves the service provided by the cooperative partners. The analysis of the processes of risk assessment of the cooperative allows establish an emergency plan that is appropriate and helpful to the needs thereof; for this purpose the methods and techniques (interview and survey) revealed both operational and financial shortcomings that prevent to meet the desired objectives was used. This plan aims to achieve positive results as a basis for decision-making by the administration and, thus allowing the survival of the company and greater confidence in the partners at the granting time of microcredits. The implementation of policies, strategies and actions, such as collection processes aimed at the recovery of microfinance will solve the problems encountered in performing loans, which will help to have greater solvency, liquidity and normal operation of the Ambato credit union Ltda.